Bestiarum vocabulum. - Kok, Shi Chun. (2012)
The human form as a subject of celebration and beauty has withstood the passage of time, whether in literature, dance, sculptures, paintings or other visual arts. Even as humans continue to discover new life and matter or conjure new aesthetics, celebration of the human form remains uncontested. From the humanoid portrayals of Egyptian gods to the peak of portraiture in Renaissance to modern day’s continuous artworks based on exploration of the human form, one may start to question why most humans throughout the ages never seemed to want to step out of this tradition. Perhaps it is the proud conscious in humans that needs to proclaim itself the epitome of beauty or perhaps it is something that had been decided through evolution and nature.